Theranostic Heterodimeric Prodrug with Dual‐Channel Fluorescence Turn‐On and Dual‐Prodrug Activation for Synergistic Cancer Therapy. Issue 21 (28th August 2021) - Jiang, Maolin; Wang, Kewei; Xiao, Xuan; Zong, Qingyu; Zheng, Rui; Yuan, Youyong
Abstract: Theranostic prodrugs that can precisely monitor drug activation with synergistic therapeutic effects are highly desirable for personalized medicine. In this study, a theranostic heterodimeric prodrug, CyNH‐SS‐DOX, with synchronous and independent dual‐channel fluorescence turn‐on and dual‐prodrug activation for synergistic cancer therapy is developed. A hemicyanine fluorescent drug, CyNH2, with good therapeutic effects found in this work, is conjugated to doxorubicin (DOX) through a disulfide linker to form CyNH‐SS‐DOX. Before activation, both the fluorescence of DOX and CyNH2 are in the off state and the toxicity is low. In the presence of intracellular glutathione, both the fluorescence of DOX and CyNH2 at different channels are turned on. Meanwhile, DOX and CyNH2 are activated in a synergistic anticancer effect. It is believed that CyNH‐SS‐DOX is promising for monitoring prodrug activation in dual‐fluorescence channels and for enhancing therapeutic efficacy with few side effects. Abstract : A theranostic heterodimeric prodrug, CyNH‐SS‐DOX, with synchronous and independent dual‐channel fluorescence turn‐on and dual‐prodrug activation is developed for synergistic cancer therapy.